Bismarck's first war : the campaign of Schleswig and Jutland 1864 - Embree, Michael (Solihull : Helion, 2006)
This book chronicles the final conflict over the now almost forgotten "Schleswig-Holstein Question", once a pivotal issue for the great powers of Europe. The campaign of Schleswig and Jutland was also the first of Otto von Bismarck's Wars of German Unification, which together created a united German Empire under Prussian leadership. The detailed story of this, the last of the "Cabinet Wars", is told here for the first time in English, compiled from numerous published and unpublished sources, including many contemporary and first hand accounts, as well as official reports. This is an invaluable.
XVII: Order of Battle, Prussian Combined III Corps April 26th 1864XVIII: Order of Battle, Combined Division Münster April 20th 1864.; XIX: Order of Battle, Royal Danish Army June 26th 1864; XX: Danish Army Combatants with Designated Units Au gust 1st1864; A Note on Sources; Bibliography; Index.
Includes bibliographical references (pages 424-450)-and indexes.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Schleswig-Holstein War, 1864.; Denmark -- History -- 1849-1866.; Guerre des Duchés, 1864.; Danemark -- Histoire -- 1849-1866.; HISTORY -- Europe -- Germany; Denmark; Deutsch-Dänischer Krieg; Dansk-tyska kriget 1864.; 1849-1866; History